Developing skills, knowledge and capacities through innovation : e-learning, m-learning, cloud learning (UN New YorkUS, 2014)
Discusses technological trends in the field of e-learning for development, in particular, cloud learning, massive open online courses (MOOCs) and m-learning.
Keywords: HUMAN RESOURCES DEVELOPMENT